Analisis Tingkat Kepuasan Konsumen Terhadap Pelayanan PT. Jaya Trade Cabang Belawan - Ricky Kurniawan; Satria Tirtayasa; Hazmanan Khair (CERED Indonesia Institute, 2021)
The approach used is descriptive quantitative where data analysis techniques are a way of collecting and clarifying information related to the problem under study. And the sample used is a saturated sample where 60 individuals from 30 consumer companies become the test population. To measure the dimensions and indicators used measures of validity and reliability, service quality is divided into 5 dimensions and 25 indicators so that the degree of service quality is in accordance with consumer perceptions and expectations to produce customer satisfaction. What needs to be covered for quadrant II is 24-hour office operations, providing a team that is always available to manage customers, ensuring protection of product distribution, on-time delivery of goods, speed of consumer response are positive perceptions that need to be preserved. Quadrant III is the assurance dimension where customer attention and feedback is handled quickly, the organization reacts to customers very quickly, provides clear communication to customers, speed of problem solving time, employee responsiveness to operational problems is continuously improved for performance improvement. To achieve greater customer satisfaction, quadrant IV on the dimensions of empathy, changes and improvements must be made.